Co-Integration Testing, Using the Johansen Method, Between General Indicators of Some Arab Financial Markets in Asia - Alawneh, Ateyah (International Journal of Asian Social Science, 2019)
The study aims to examine Co-integration by using the Johansen method between general indicators of some Arab Financial Markets in Asia. The study uses monthly data of the general indicators of stocks in Arab financial markets for the period from 2010-2017. In order to achieve the objectives of the study, the researcher examined the stationary of the indicators. In this regard, all indicators were found stable at the first difference. As a result, the data have met the first condition of co- integration investigation. The study found that the lag period is zero according to (schware) test. Moreover, the analysis of co- integration by testing the Co-integration Rank and the Maximum Eigen value showed the existence of one co- integration at least between Arab Financial Markets in Asia. The study provides a number of recommendations; the most important of which is to support more capital flows between the markets and to use attractive financial instruments for investors in the Arab Financial Markets in Asia. This can be done through the extensive use of Islamic financial instruments. Furthermore, the current paper aims at establishing a monetary integration between the study samples.